ASSESSMENT OF POTENTIAL HUMAN HEALTH RISKS FROM SOME HEAVY METALS AND ARSENIC VIA FISH CONSUMPTION - Canpolat, Ozgur (Parlar Scientific Publications (P S P), 2020)
The main objectives of this study were (1) to assessment the non carcinogenic health hazard and cancer risk estimated with some heavy metals via consumption of Capoeta umbla from the Keban Dam Lake (Turkey) using the target hazard quotient (THQ), hazard index (HI) and carcinogenic risks (CR) from heavy metals and (2) to determine the concentrations of As, Fe, Cu, Zn, Cr, Cd, Ca, Mg, Na and K in some tissue of C. umbla. In general, the lowest concentrations of these elements determined in the muscle compared with skin, gonad, kidney, gill and liver. The amounts of heavy metals in the muscle of C. umbla were found lower than that recommended by EPA, WHO and FAO. In this study, the THQ and HI values of the heavy metals determined in C. umbla was smaller than the threshold value of 1. This show that there are no health risk for non-cancer. Cancer risk (CR) was also calculated for inorganic arsenic by using cancer slope factor. The cancer risk (CR) value for inorganic As (iAs) found below 10(-6) . This result indicating no cancer risk. According to these results, the consumption of C. urnbla in this dam lake is safe for human consumption.
Keywords: Heavy metals; Arsenic; Cancer risk; Non carcinogenic health hazard; Fish consumption; Capoeta umbla